Synthesis of Novel 3,19-Dihydroxyjolkinolides and Related Derivatives Starting from Andrographolide - Wang, Ke; Wu, Yang-Chang; Yang, Juan-Cheng; Zhang, Meng-Han; El-Shazly, Mohamed; Zhang, Da-Yong; Wu, Xiao-Ming (Synthesis, 2016)
The jolkinolides are a series of naturally occurring ent-abietane diterpenes with potent antitumor activity, which have been isolated from the genus Euphorbia. We describe the first method for the total synthesis of 3,19-dihydroxyjolkinolide and its derivatives. The strategy for the synthesis of 3,19-dihydroxyjolkinolide A has 12 steps with an overall yield of 4.3%. The synthesized compounds were evaluated for their antitumor activity in nine kinds of tumor cell lines.
Keywords: ent-abietane diterpenes; jolkinolides; andrographolide; Wittig–Horner reaction; antitumor evaluation